2016
DOI: 10.1080/15384047.2016.1264540
|View full text |Cite
|
Sign up to set email alerts
|

Phenethyl isothiocyanate suppresses the metastasis of ovarian cancer associated with the inhibition of CRM1-mediated nuclear export and mTOR-STAT3 pathway

Abstract: Epithelial ovarian cancer is prone to metastasizing at an early stage, but their mechanisms remain unclear. CRM1 is an important nuclear exportin and inhibitors targeting CRM1 has been explored as an anti-cancer strategy. In previous study, we observed that PEITC could combine with the hydrophobic pocket of CRM1. In this study, we focused on the effects of PEITC on EOC and its mechanisms. Results showed that IC 50 values of PEITC on SKOV3 and HO8910 cell line were 42.14 mM and 37.29 mM, respectively. PEITC inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…Our previous study showed that PEITC and BITC suppress metastasis potential of lung cancer cells . Interestingly, other groups also revealed the inhibitory effect of isothiocyanates on metastasis in ovarian cancer, prostate cancer, breast cancer, and cervical carcinoma . Although these studies indicated that several mechanisms are involved, such as the inhibition of CRM1‐mediated nuclear export and mTOR‐STAT3 pathway, regulation on miRNA‐194, and involvement of HIF‐1alpha, however, the role of autophagy has not been elucidated.…”
Section: Discussionmentioning
confidence: 98%
“…Our previous study showed that PEITC and BITC suppress metastasis potential of lung cancer cells . Interestingly, other groups also revealed the inhibitory effect of isothiocyanates on metastasis in ovarian cancer, prostate cancer, breast cancer, and cervical carcinoma . Although these studies indicated that several mechanisms are involved, such as the inhibition of CRM1‐mediated nuclear export and mTOR‐STAT3 pathway, regulation on miRNA‐194, and involvement of HIF‐1alpha, however, the role of autophagy has not been elucidated.…”
Section: Discussionmentioning
confidence: 98%
“…mTOR over-activation can cause OC and it is also related to ovarian diseases such as polycystic ovarian syndrome [ 67 ]. The mTOR is caught up in OC metastasis and its inhibition causes suppression of OC metastasis [ 68 ]. CCL18, a chemotactic cytokine, causes cancer and thought to be a biomarker for epithelial OC.…”
Section: Interrelation Of Pi3k/akt/mtor and Pim Pathways In Ovariamentioning
confidence: 99%
“…Previous reports have suggested that STAT3 is persistently activated through constant nucleocytoplasmic shuttling, which is regulated by CRM1 [48,49]. STAT3 contains several NES elements through which it binds to CRM1 for nuclear export [49,50]. Inhibition of CRM1-mediated nuclear export can slow down the nucleocytoplasmic shuttling of activated STAT3 resulting in reduced tyrosine phosphorylation, decreased induction of STAT3 target genes, and increased apoptosis [51].…”
Section: Discussionmentioning
confidence: 99%